The Effect of Early Breastfeeding Initiation (IMD) on Changes in Blood Pressure of Mothers in Hypertension - Eftyaningrum Dwi Wahyu Astutik; Endah Purwanti Handayani; Yustika Rahmawati Pratami; Wiwit Vitania; Arum Surya Utami (Indonesian Journal of Global Health Research, 2026)
Hypertension in pregnancy is one of the reason main maternal morbidity and mortality. Suboptimal treatment can increase risk postpartum complications. Initiation Early Breastfeeding (IMD) is suspected own effect physiological in lower pressure blood through release oxytocin triggers relaxation and vasodilation. However, evidence empirical about the influence of IMD on change pressure blood in the mother giving birth with hypertension Still limited. Analyze influence action Initiation Early Breastfeeding (IMD) against change pressure blood in the mother giving birth with hypertension. Study quasi-experiment with design pretest–posttest control group design conducted on 60 mothers giving birth with hypertension, consisting of from the right IMD group time (n=30) and slow IMD (n=30). The sampling technique used was purposive sampling. Pressure blood systole and diastole are measured before and after IMD action. Normality test use Kolmogorov–Smirnov, and the differences before after analyzed use paired t-test. The right IMD group time show decline significant pressure blood systolic (mean 2.5 mmHg; p=0.000) and diastolic (mean 2.63 mmHg; p=0.001). In the slow IMD group, the decrease pressure blood systolic (0.3 mmHg; p=0.510) and diastolic (1.1 mmHg; p=0.068) were not significant. Correlation test obtained p=0.000 both at pressure blood systole and pressure diastolic blood pressure in the IMD group was correct time. IMD is right time effective lower pressure blood systole and diastole significant in mothers giving birth with hypertension compared to slow IMD. IMD has the potential become safe and beneficial non - pharmacological interventions for stabilization postpartum hemodynamics.